THU0254 ARTICULAR INVOLVEMENT, STEROID TREATMENT AND FIBROMYALGIA ARE THE MAIN DETERMINANTS OF PATIENT-PHYSICIAN DISCORDANCE IN SYSTEMIC LUPUS ERYTHEMATOSUS. (2nd June 2020) - Elefante, E.; Tani, C.; Ferro, F.; Stagnaro, C.; Parma, A.; Signorini, V.; Zucchi, D.; Poli, V.; Carli, L.; Mosca, M.
Abstract : Background: Remission or the lowest possible disease activity are the main targets in the management of Systemic Lupus Erythematosus (SLE). Anyway, conflicting data are present in the literature regarding the correlation between physician-driven definitions and patient perception of the disease. The discordance between patient and physician perspectives may have a negative impact on disease outcomes. Objectives: The aim of this study was to identify the main determinants of patient-physician discordance in the evaluation of SLE and health status. Methods: This is a cross-sectional study that enrolls patients with a diagnosis of SLE (ACR 1997 criteria). For each patient, demographics, comorbidities, treatment, clinical and laboratory data were collected. Disease activity was evaluated with the SELENA-SLEDAI score and organ damage with the SLICC/DI. Patients included have been categorized according to the following categories: remission, on or off treatment 1, low disease activity (LLDAS) 2 and active disease status. At enrollment, each patient completed the following PROs: SF-36, FACIT-Fatigue, LIT and SLAQ. We defined a SLAQ score<6, corresponding to the 25° percentile of our cohort, as the cut-off value to define a low disease activity state according to the patient self-evaluation. Results: We enrolled 259 consecutive adult SLE patients (93.05% female, 97.2% Caucasian, mean age 45.33±13.14 years, median disease duration 14 years (IQR 6-21)). 208/259 patients satisfied the definition of LLDAS and among them 171 were in remission; 51/259 patients were active. No significant differences emerged as for the results of PROs between groups. Considering the subgroup of 208 patients in LLDAS, we identified 56 patients with a subjective condition of low disease activity (SLAQ<6) and we defined them as "concordant"; the remaining 152 patients in LLDAS presented a subjective active disease (SLAQ≥6) and we defined them as "discordant". Comparing these two groups, we found that "discordant" patients had more frequently ongoing and past joint involvement (p<0.05) and a concomitant diagnosis of fibromyalgia (p<0.01); finally, they were more frequently on glucocorticoid therapy (p<0.01). "Discordant" patients showed a significantly worse quality of life, evaluated by all PROs (p<0.0001) (Tab 1). Conclusion: Articular involvement, fibromyalgia and ongoing glucocorticoid treatment, even at low dose, are the major determinants of patient-physician discordance in SLE, determining a negative patient perception of health status. References: [1]van Vollenhoven R, et al. Ann Rheum Dis 2017 - Review. PMID 27884822; [2]Franklyn K, et al. Ann Rheum Dis 2016. PMID 26458737 Disclosure of Interests: None declared